Perayaan Tahun Baru Masehi: Tinjauan Hermeneutika Dekonstruksi Jacques Derrida - Badrud Tamam (KOLONI, 2023)
The purpose of this study is to review various aspects regarding the celebration of the Christian New Year in the view of Deconstructive Hermeneutics, a theory initiated by the German philosopher Jacques Derrida. The method considered is using descriptive-qualitative approach with literature and history. There are many views regarding the celebration of the Christian New Year in terms of meaning and implementation in the field from various points of view, such as religious figures, humanists, and others, resulting in various conclusions and claims. Hermeneutics as the art of understanding a text or phenomenon can provide a new perspective on several phenomena that occur when the New Year is celebrated. Many from various circles celebrate it as an enthusiastic form of the end of the year and the start of a new chapter in a life. Especially in the fact that this moment is filled with a variety of cultural and habitual contents so that it creates the perception that the New Year is an important moment that cannot be let go throughout the year. For some elements, New Year is often considered as a sacred day in their lives. The end of this research is expected to find comparisons between points of view from various aspects.